Analysis of The Ball Joints Rolling Process Deformation - Roslizan, Mohammad Fithri; Sulaiman, Syabillah (Progress in Engineering Application and Technology, 2020)
Ball joint is a part of car suspension system. Analysis of ball joint deformation by using Finite Element Analysis (FEA) were study. Rolling process assemblies is a way of ball joints to obtain rotating torque. Good deformation process produces a good quality of a ball joint. Bad quality of ball joint can cause a failure to a vehicle control arm. Normally if the ball joint deformation is unfinished, the output of ball joint produce out of specification rotating torque. Unfinished deformation of the ball joint is dangerous, it will make a safety problem. Every ball joint have different dimension, every dimension required different jig and fixture in the production line. Right load apply will make good deformation. Due to the pandemic situation full data as per primary objective can’t be achieve. The result of the study may be less because to develop automatic roller size selection and to study torque required site visit to the manufacturing line production. In this study, using SIMULIA Abaqus software can determined the right position to apply rolling load and mimic the deformation by using the simulation process.